Sustainable small-scale mining through geological and resource estimation: a holistic, society-centred approach - Mahlaule, Ntiyiso Ally; Sengani, Fhatuwani; Rapholo, Maropene Tebello Dina (Journal of Degraded and Mining Lands Management, 2026)
Sustainable small-scale mining (SSM) development presents both challenges and opportunities for stone resource economies. Having been characterised by informality, a lack of technology, and environmental degradation, SSM remains a significant global producer of geological raw materials, including stone resources. However, it often struggles with the appraisal of resources and the classification of reserves. Conventional geological methods, although effective, are not being considered. This study examined the traditional estimation of the contribution of stone techniques to sustainability and resource estimation in small-scale industries. Babanana Greyfield at Meadowbank Farm was selected as a case study area due to its accessibility and the availability of borehole information. Rotary drilling, core logging, and Avanza Solution methods were employed to collect the data necessary for constructing geological maps and cross-sections. Maptek Vulcan Quarry Modeller was also employed for 3-D modelling and estimation of stone resources. Results revealed that these techniques efficiently improved volume calculation, tonnage, resource, and reserve estimation. These traditional techniques have been proven to enhance accuracy, minimise environmental impact, and facilitate strategic planning when applied effectively. Nevertheless, financial and technical constraints persist. The validation of the methods used in the study revealed a 99.99% performance score. Thus, this study is considered highly reliable, as evidenced by the near-total concordance between the predicted and actual volumes, which implies great internal consistency in this study and hence reproducibility. The research suggests that training initiatives should focus on specific requirements, low-technology expenditure, and organisation by agencies such as ASPASA, the Department of Mineral Resources and Energy, and the Council for Geoscience to implement sustainable methods.